Green and clean campus melalui sosialisasi pengelolaan sampah dan limbah organik terpadu berkelanjutan: Green and clean program through socialization sustainable integrated waste management and composting - Ikawati Karim; Widyanti Utami A.; Andi Werawe Angka; Kasmiati Kasmiati; Andi Mawadda Zakiyah; Weni Anggraini Adhisty; Muhammad Nasir Badu (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2026)
Waste is one of the main issues in environmental pollution. Therefore, ineffective and inefficient waste management can potentially damage the environment, such as waste decomposition, which causes health risks. Universitas Sulawesi Barat as the locus of ongoing activities, experiences various problems in its waste management. The large amount of waste scattered on campus is due to the lack of awareness of stakeholders, including students and canteen managers, as the largest contributors to waste. The absence of garbage pickup trucks on campus has made waste management ineffective, and waste is often burned on campus, which can have serious health impacts if the smoke is inhaled. Therefore, various stages of program activities were carried out from July to September 2025, starting with program socialization to stakeholders, namely PT. Kencana Hijau Bina Lingkungan (KHBL) Polewali Mandar, conducting socialization with the theme